Peran Guru Pendidikan Agama Islam terhadap Siswa yang Kesulitan Baca Tulis Al-Quran di SMP Negeri IV Koto - Nurhazizah Nurhazizah; Hidra Ariza; Nurfatmi Nurfatmi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The aim of this research is to determine the role of understanding Islamic religious education for students who have difficulty reading and writing the Koran at SMP Negeri IV Koto. The research method used is a qualitative approach. By collecting data through observation, interviews and documentation. Interviews were conducted with Islamic religious education teachers and other teachers involved in the process of helping students overcome their difficulties in reading and writing the Koran. This research shows that Islamic religious education plays an important role in helping students overcome difficulties in reading and writing the Koran. Elements such as a structured curriculum, interactive learning, and quality teacher support are very helpful in improving students' ability to master reading and writing the Koran. These results provide a better picture of the importance of Islamic religious education in schools and can serve as a guide to further improve Al-Quran education at SMP Negeri IV Koto School.